Customers’ attitude upon diminishing partnership home financing in Islamic banking - Abduh, Muhamad; Abdul Razak, Dzuljastri (2013)
Problem statement: Diminishing partnership or musharakah mutanaqisah contract in home financing is recently introduced by the Islamic banking industry as an alternative of the bay bi’thaman ajil contract which has received many criticism from shariah scholars as mimicking conventional loan. This study aims to examine customers’ attitude upon diminishing partnership home financing and their intention to subscribe into the financing scheme. Approach: This study gauges customers’ perception on the salient features of diminishing partnership home financing from Islamic banks through a survey of 504 respondents comprise officers, managers and academician in Kuala Lumpur. The structural equation modeling was utilized to find out factors that influence customers’ intention for diminishing partnership home financing under the framework of the theory of reasoned action. Results: The main finding indicates that customers perceived the equity sharing features in diminishing partnership home financing mode differ from the conventional loan and other existing Islamic home financing modes. The result from structural equation modeling shows that customers’ intention for diminishing partnership is more influenced by their subjective norms compared to their attitude toward diminishing partnership home financing. Conclusion: The customers have perceived diminishing partnership as more shariah compliant than bay bi’thaman ajil. Afterwards, opinions from people perceived important by customers are giving more influence towards their decision making process.